O efeito do capital humano em doenças epidemiológicas selecionadas : AIDS, hanseníase e tuberculose - Rodrigues, Juliano Ricardo Alves (2009)
The objective of this paper is proposing a model to study the interaction between epidemiological diseases and human capital (education), taking Grossman (1972a, 1972b) papers as basis. It has been estimated a function to inferring such relationship using econometric panel data technique for all Brazilian states with data from 1997 to 2006. As endogenous variables it has been taken AIDS, leprosy and tuberculosis diseases incidence rates. Results have shown an inverse relationship between the variables. In other words, increased levels of human capital (education) contribute to reduce the studied diseases incidence rate, which is in agreement to the proposed model. The education level which helps reducing AIDS disease incidence rate range from 1 to 3 years of study and for both leprosy and tuberculosis diseases the range vary from 4 to 7 years of study.